Electrical conductivity and thermoelectrical parameters of argyrodite-type Cu7−𝑥PS6−𝑥I𝑥 mixed crystals - Pogodin Artem; Погодін Артем; Luchynets Mykhailo; Лучинець Михайло; Filep Mykhailo; Філеп Михайло; Filep Mihály; Anton Kohutych; Когутич Антон; Malakhovska Tetyana; Малаховська Тетяна; Oleksandr Kokhan; et al. (My University, 2021)
Abstract. Cu7−𝑥PS6−𝑥I𝑥mixed crystals were grown by the direct crystallization from a melt. The electrical conductivity is measured in the frequency range from 10 Hz to 300 kHz and in the temperature interval 293–383 K. The frequency, temperature, and compositional dependences of the electrical conductivity for Cu7−𝑥PS6−𝑥I𝑥 mixed crystals are studied. The measurements of thermoelectric parameters of Cu7−𝑥PS6−𝑥I𝑥mixed crystals are carried out in the temperature interval 293–383 K. The compositional behaviors of the electrical conductivity, activation energy, Seebeck coefficient, and power factor are investigated. The interrelation between the structural, electrical, and thermoelectrical properties is analyzed.

Резюме. Методом спрямованої кристалiзацiї з розплаву вирощено монокристали твердих розчинiв Cu7−𝑥PS6−𝑥I𝑥. Електрична провiднiсть вимiрювалася у частотному дiапазонi 10 Гц–300 кГц та в iнтервалi температур 293–383 K. Дослiджено концентрацiйну, частотну та температурну залежностi електричної провiдностi монокристалiв твердихрозчинiв Cu7−𝑥PS6−𝑥I𝑥. Вимiрювання термоелектричних параметрiв монокристалiв Cu7−𝑥PS6−𝑥I𝑥 проводились у температурному iнтервалi 293–383 K. Вивчено концентрацiйну поведiнку електричної провiдностi, енергiї активацiї, коефiцiєнта Зеєбека та термоелектричної потужностi. Проаналiзовано взаємозв’язок структурних, електричних та термоелектричних властивостей твердих розчинiв Cu7−𝑥PS6−𝑥I𝑥.
Електрична провiднiсть та термоелектричнi параметри твердих розчинiв зi структурою аргiродиту Cu7−𝑥PS6−𝑥I𝑥
Contents: https://ujp.bitp.kiev.ua/index.php/ujp/issue/view/104 Editorial Team: https://ujp.bitp.kiev.ua/index.php/ujp/about/editorialTeam
Keywords: mixed crystals; electrical conductivity; activation energy; Seebeck coefficient; power factor; compositional dependence